Gravity Model and International Trade: A Survey of the Literature - Nuno Carlos Leitão (2024)
The gravity model, which is applied to international trade, explains the conceptual models of international business. It has been used in various areas of the global economy, such as trade, foreign direct investment, and even the determinants of tourist demand at the level of countries and sectors of economic activity. In terms of the methodology, this study of the gravity model followed the PRISMA requirements and bibliometric analysis (co-occurrence of keywords and network of co-authorship), which were applied to the Scopus database. In terms of the results, economic, geographical distance, and location variables are essential in explaining international trade.